Implementasi Blue Ocean Strategy untuk Menciptakan Value Innovation di Elmaskin Aesthetic and Anti-Aging Clinic - Mochammad Atiq Kurniawan; Eric Harianto; David Sukardi; Tommy C. Efrata (Journal of Economics and Management Scienties, 2026)
The aesthetic clinic industry in Surabaya is characterized by intense competition, homogeneous treatment offerings, price-driven promotions, and growing customer expectations for transparent and personalized services. This study aimed to design and implement an innovation strategy grounded in Blue Ocean Strategy to create value innovation at Elmaskin Aesthetic & Anti-Aging Clinic. A descriptive qualitative approach with a project-based research design was employed. Data were collected through in-depth interviews, observations, and document analysis involving ten informants selected through purposive sampling, including representatives of management, doctors, nurses, customers, competitors, and aesthetic clinic industry expert. The data were analyzed using SWOT Analysis, Key Success Factors, Strategy Canvas, Four Actions Framework, and Six Paths Framework. The study developed the Elmaskin Transparent & Personalized Beauty Journey, which transforms conventional treatment transactions into a transparent, personalized, educational, and continuous care journey. The concept was operationalized through eight integrated strategies: brand positioning, personalized programs, treatment development, membership optimization, customer relationship management, information transparency, omnichannel marketing, and digitalization of forms. Initial implementation increased customer satisfaction from 82.2% to 94.3%, average returning-patient visits by 11.5%, and the number of new patients by 8.2%. Revenue in May 2026 was also 5.6% higher than the pre-implementation average. These findings suggest that information transparency, service personalization, and continuity across the customer journey can create a differentiated value curve in the aesthetic clinic industry.